Gamified Motor Training With Tangible Robots in Older Adults: A Feasibility Study and Comparison With the Young - Guneysu Ozgur, Arzu; Wessel, Maximilian J.; Olsen, Jennifer K.; Johal, Wafa; Ozgur, Ayberk; Hummel, Friedhelm C.; Dillenbourg, Pierre (Frontiers in Aging Neuroscience, 2020)
Background: The increasing lifespan and the resulting change of our expectations in later life stages are dependent on a good health state. This emphasizes the development of strategies to further healthy ageing. One important aspect of good health in later life stages is sustained skilled motor function. Objective: Here, we tested the effectiveness of robotic upper limb motor training in a game-like scenario assessing game-based learning and its transfer potential. Methods: Thirty-six healthy participants (n = 18 elderly participants, n = 18 young controls) trained with a Pacman-like game using a hand-held Cellulo robot on two consecutive days. The game-related movements were conducted on a printed map displaying a maze and targets that had to be collected. Gradually, the task difficulty was adjusted between games by modifying or adding different game elements (e.g., speed and number of chasing ghosts, additional rules, haptic feedback). Transfer was assessed by scoring simple robot manipulation on two different trajectories. Results: Elderly participants were able to improve their game performance over time (t(874) = 2.97, p < .01). The applied game-elements had similar effects on both age groups. Importantly, the game-based learning transferred to simple robot manipulation, which resembles activities of daily life. Only minor age-related differences were present (smaller overall learning gain, different effect of the wall crash penalty rule in the elderly group). Conclusions: Gamified motor training with the Cellulo system has the potential to translate into an efficient, relatively low-cost robotic motor training tool for promoting upper limb function to promote healthy aging.